Effects of the mass parameter in the optimum direction of impulse and energy variation in a Powered Swing-By - Ferreira, A. F.S. [UNESP]; Moraes, R. V. [UNESP]; Prado, A. F.B.A.; Winter, O. C. [UNESP] (IOP Publishing, 2019)
The energy of a spacecraft, relative to the primary body of the system, before and after a Powered Swing-By maneuver with an impulse applied during the close encounter with the secondary body is studied. The Powered Swing-By maneuver is a combination of the effect of the gravity of a celestial body and an impulse applied to the spacecraft during its passage by the periapsis of its orbit relative to the secondary body. This combination modifies the spacecraft's trajectory, changing its parameters and, consequently, its energy. The objective is to quantify the effect of different mass parameters on the optimum direction to apply the impulse and in the energy variation of this more complex maneuver. It is focused on the two-dimensional and elliptical maneuver. Optimum solutions for energy gains are presented.